Preparation and Characterization of Acid and Alkaline Treated Kaolin Clay - Sachin Kumar; Achyut Kumar Panda; R. K. Singh (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
Kaolin was refluxed with HNO3, HCl, H3PO4, CH3COOH, and NaOH of 3M concentration at 110 °C for 4 hours followed by calcination at 550 °C for 2 hours. The physico-chemical characteristics of resulted leached kaolinite clay were studied by XRF, XRD, FTIR, TGA, DTA, SEM and N2 adsorption techniques. XRF and FTIR study indicate that acid treatment under reflux conditions lead to the removal of the octahedral Al3+ cations along with other impurities. XRD of acid treated clay shows that, the peak intensity was found to decrease. Extent of leaching of Al3+ ions is different for different acid/base treatment. The acid treatment increased the Si/Al ratio, surface area and pore volume of the clay. Thus, the treated kaolin clay can be used as promising adsorbent and catalyst supports. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)